The Importance of Anterior Segment Reconstruction after Severe Bilateral Open Globe Injury for Visual Acuity Outcome – Case Report - Kopacz, Dorota; Maciejewicz, Piotr; Kopacz, Amelia H. (New Frontiers in Medicine and Medical Research Vol. 14, 2021)
Open globe injuries are one of the major causes of visual impairment and blindness. Achieving useful visual acuity depends on several factors such as initial visual acuity, presence of relative afferent pupillary defect, mechanism and severity of injury, involvement of ocular structures and proper, prompt diagnosis and treatment. We present a case of a 48-year-old man with bilateral open globe injury to show that poor initial visual acuity does not exclude final useful acuity. In our case severity of the trauma and poor visual acuity were detrimental prognostic factors for visual acuity outcome. Within long-term follow-up with additional surgery procedures of both eyes we have reached a significant visual acuity improvement.